Lead poisoning in a 6-month-old infant: a case report - Duan, Yifei; Yan, Lingyi; Gao, Zhengxiang; Gou, Yu (Frontiers in Public Health, 2023)
Background: Lead is a toxic element of the environment that leads to major complications once it enters the blood stream, affecting multiple organs and systems of the body. Methods: We present a case of a 6-month-old female infant diagnosed with lead poisoning after presenting for routine child health care. The child’s mother denied that the infant had a history of exposure to lead-containing substances. After a month of calcium supplementation, the patient’s blood lead level remained elevated. We then tested the blood lead level of the mother and father. The results showed that the blood lead level of the mother was 77.0 μg/L and that of the father was 36.9 μg/L. The high blood lead level of the mother attracted our attention. We found that the mother had been using an external traditional Chinese medicine, Hu Wang Fen, which contains lead. After the mother’s discontinuation of use of the traditional medicine, the child was treated with symptomatic treatment and chelation therapy. Subsequently, the patient’s blood lead level decreased significantly. Results: Lead toxicity can be a life-threatening problem because of its potential for severe complications. In children, there is no safe blood lead level, and the toxic effects of lead can be prevented by the awareness and avoidance of traditional Chinese medicines that may contain lead. Conclusion: Even though the diagnosis of lead poisoning remains difficult in children, it must be taken into consideration by the clinician when treating a child using traditional Chinese medicines.